Community Empowerment and Farmer Poverty Reduction in Developing Countries - Budi Permadi (JPAS (Journal of Public Administration Studies), 2019)
Farmer community empowerment in agriculture development plays a significant role. Community empowerment is expected to reduce poverty, especially among farmers. The purpose of this paper is to summarize what are the causes of farmer poverty and what efforts have been made regarding community empowerment, to alleviate the poverty in the developing countries, especially in Indonesia and Ghana. This study used literature review approach to conduct a brief review of community empowerment and farmer poverty reduction. The results obtained, based on literature reviews and analyses, are the causes of farmer poverty such as low investment ability of farmers, dependence of farmers, dependence on funds, non-fulfillment of basic needs of farmer households, inadequate access to finance and extension services, etc. The findings suggest the programs to alleviate farmer poverty such as market creation for farmers, establishing or activating the Farmers Group, farmers group assistance, a program to procure demonstration field in each village, training, counseling, network formation, providing loan, etc.